Thermochemical measurement of the ligand field splitting energies for hexaaquo complexes of Mn (II), Ni (II) and Zn (II) ions in the Tutton's salts - Muhammad, Badri; Ibrahim, W.; Crouse, Karen Anne (1980)
Various high-energy modification and crystalline hydrates of Tutton's salts containing Mn(II), Ni(II) and Zn(II) have been prepared and their heats of solution measured. The energy difference of the anhydrous salts given in kJ/mole of hexahydrate have been assigned as 10Dqs for the complexes. The values obtained have been compared with the ligand field splitting energies of the complexes in the sulphate salts. The discrepancies were explained in terms of the presence of ammonium ions in the lattice which may have reduced the electron density on the coordinated water molecules.